(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The term Eco-criticism is obviously used for the observation and learning the relationship between the literature and the environment. Human beings interact with various aspects of the nature and so their lives are inextricably bound with non-human beings and other fellow human beings. The American writer Barbara Kingsolver the doyenne of ecofeminism synthesizes her feminist concerns with ecological belief in her fiction. In Prodigal Summer Kingsolver communicates a deep and abiding love and regards for the land. The interconnectedness of the flora, fauna and human world are presented in this fiction. The fiction centers around the story of three characters, who live near Egg Fork in the Sothern Appalachian mountain range. Women in the novel are portrayed as conservationist, who protect and preserve the environment and wildlife. Comparatively the contribution of women to nature is far better than the males. Men treat the land as a tool for agriculture and symbol of status, and they often consider that it is under their control and they can utilize it without giving much concern of the consequences. Whereas, the women characters in the fiction discuss on how to redeem their ecology with their tactful ideas and deeds. The women recognize the intersectional reality of human and non-human lives, whereas the males often fail to recognize that fact and perpetuate patriarchal, exploitive practice. The present paper aims at analysing how the female members of Prodigal Summer sympathize or empathize with the environment and show their greater state of ecological awareness.